MINAT BELAJAR MAHASISWA PGSD PADA MATA KULIAH KONSEP DASAR IPA (Penelitian Deskriptif Kualitatif di Prodi PGSD Universitas Muhammadiyah Tasikmalaya) - Mohammad Fahmi Nugraha; Budi Hendrawan (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2019)
This study uses descriptive qualitative research with case study approach, according to Kumar (1999), a case study is an approach to examine social phenomena through the analysis of individual cases completely and accurately, as well as providing an analysis of intensive than many specific details that are often overlooked by Other research methods. Meanwhile, according to Pollit and Hungler (1999) interpret the case study as a research method that uses in-depth analysis, which is done carefully and completely to an individual, family, group, institution, or other social units. The results showed interest in learning PGSD students on the course the basic concepts of science is low, the study documentation on the midtest course the basic concepts of science and interviews explaining there are several factors that affect low interest student learning is the educational background of students, the ability of lecturers, weight and material science courses basic concepts, means of supporting lectures and lecture schedule.